On The Extended Blazar Sequence For γ-Ray Emitting Active Galactic Nuclei - Audu, A. I.; Odo, F. C.; Ubachukwu, A. A.
In this paper, we use the distributions of observed y -ray properties, as well as orientation parameters of a sample of Fermi-LAT AGNs to investigate the hypothesis that y -NLS1 objects are beamed sources with y -ray emitting axes inclined at close angles to the line of sight. Based on these parameters we investigate the relationship between y- ray emitting jetted AGNs. Results show that y -NLS1s are more highly beamed than both FSRQs and BL Lacs with mean value of core-dominance parameter Rg ~ 9507. y --NLS1s and jetted Seyfert galaxies are continuous in distribution of the orientation parameter with average cone angles Ôm ~ 8o and 44o respectively. Furthermore, the spectral energy distribution of y NLS1 is comparable to those of FSRQs and BL Lacs suggestive that y-NLS1s and blazars form a continuous spectral sequence. There is a significant anti-correlation (r ~ -0.9) between the y -ray luminosity There is a strong dependence of Dg on redshift (r ~ -0.7) suggestive that Dg is more sensitive to environmental factors than intrinsic y-ray luminosity. The results suggest that y--NLS1s are highly beamed counterparts can be found among Seyfert galaxy populations. В данной работе используется распределение наблюдаемых свойств y- излучения, а также параметры ориентации для выборки AGN, зарегистрированных с помощью Fermi-LAT, чтобы исследовать гипотезу о том, что объекты y-NLS1 являются источниками излучения, направленными с осями y-излучения, наклоненными под малым углом к лучу зрения. Основываясь на этих параметрах, исследована взаимосвязь между y-NLS1 и другими подтипами активных галактик с релятивистскими джетами, испускающих y-излучение Результаты показывают, что y-NLS1 более сфокусированы, чем FSRQ и BL Lac с средним значением параметра доминирования ядра Rg ~ 9507. y-NLS1 и сейфертовские галактики с джетами образуют непрерывное распределение по параметру ориентации, со средними углами конусов Фm ~ 8o и 44o, соответственно. Кроме того, спектральное распределение энергии y-NLS1 сопоставимо с распределением для FSRQ и BL Lac, что указывает на то, что y-NLS1 и блазары образуют непрерывную спектральную последовательность. Наблюдается значительная антикорреляция (r ~ -0.9) между доминированием y- излучения Dg и гамма-лучевой светимостью. Также обнаружена сильная зависимость Dg от красного смещения (r ~ -0.7), что указывает на большую чувствительность Dg к факторам окружающей среды, чем к собственной светимости y-излучения. Результаты предполагают, что y-NLS1являются сильно сфокусированными источниками y-излучения, де-фокусированные аналоги которых можно найти среди популяций сейфертовских галактик.
Keywords: Galaxies